Multidimensional analysis of clinical symptoms in patients with Fabry's disease. Issue 2 (11th January 2013) - Kaminsky, P.; Noel, E.; Jaussaud, R.; Leguy‐Seguin, V.; Hachulla, E.; Zenone, T.; Lavigne, C.; Marie, I.; Maillot, F.; Masseau, A.; Serratrice, C.; Lidove, O.
Summary Aim: Fabry's disease is an X‐linked inherited lysosomal storage disorder caused by the deficient activity of alpha‐galactosidase A. The interrelationships between clinical symptoms in Fabry patients have not yet been fully established. Using cluster and multivariate analysis, the aim of the study was to determine the relationships among clinical symptoms and organ involvement, and predictive clinical symptoms for disease severity. Methods: Clinical data obtained from 108 French Fabry patients were retrospectively collected and analysed using multiple correspondence analysis and hierachical ascendant classification. Multivariate analysis was also performed to determine among clinical symptoms predictors for cardiac disease (HRT), renal involvement (KDN) and brain complication (STR). Results: The cohort comprised 41 male patients (aged 28.9 ± 11.6 years) and 67 female patients (aged 40.4 ± 15.5 years). Three main clusters of clinical symptoms could be delineated, characterising disease progression: the first cluster grouped digestive disorders (found in 30% of the patients) and exercise intolerance (32%), the second, cluster dyshidrosis (47%), acroparesthesia (67%), angiokeratoma (44%) and cornea verticillata (54%), the third, cluster grouped KDN (30%), HRT (39%) and STR (25%) and hearing loss (44%). In univariate analysis, the patient age predicted HRT and KDN, dyshidrosis predicted HRT and STR, angiokeratoma predicted KDN and cornea verticilla and hearing loss predicted KDN, HRT and STR. In multivariate analysis, hearing loss and age were independent predictors of organ complication. Conclusion: Among the various interrelated clinical symptoms occurring in Fabry disease, patients with dyshidrosis and particularly hearing disorders appear to be at higher risk of organ complications.